Static Analysis of Frame Structure of Post-Stroke Tricycle Design Based on Solidworks Software 2012 with Material Type Variations - Eko Siswono; Mulyadi Mulyadi (R.E.M. (Rekayasa Energi Manufaktur) Jurnal, 2019)
The body weight of post-stroke patients varies from one another, this can affect material selection. In this study, the researchers designed a three-wheeled frame using various types of material and the same material size including: galvanized pipe, stainless pipe (AISI 304), mild steel pipe (ASTM A36), Alloy Steel pipe to obtain a safe design for sufferers post-stroke, the skeletal design was analyzed statically using Soliworks 2012 software to obtain the results of analysis in the form of: Von Mises Voltage, Safety Factor (Strain) and Strain (Displacement). Static analysis of Post-Stroke Tricycle Design results obtained the greatest Von Mises Voltage value on ASTM A36 type material with a stress value of 154.5 N/mm2 (MPa) and the smallest stress value in Galvanized type material with a stress value of 150.8 N/mm2 ( MPa). Based on the results of the analysis of Safety Factors (Safety of Factor) so that the design can be said to be safe for patients after stroke, the type of material that must be used is Alloy Steel with a value of Safety Factor (Safety of Factor) of 5.49.